ANALISIS PENGARUH SUB SEKTOR PERTANIAN TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI BENGKULU TAHUN 2011-2021 - Natanael; As'ad Hasan; Teguh Dwi Arsyah (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2024)
Economic growth is a process of increasing total and maximum income, per capita income of the population by taking into account the increase in population as well as fundamental changes in the economic structure of a country and equal distribution of income for the population over a long period of time. The role of the agricultural sector in development in Bengkulu Province occupies a very important position. The agricultural sector is a source of supplies of food and raw materials needed by the people of Bengkulu Province. This research uses data analysis with descriptive quantitative analysis techniques. Descriptive, namely describing and interpreting the research object. Research result The Food Crop Agriculture sub-sector has a positive influence on economic growth in Bengkulu Province. The Forestry sub-sector has a positive influence on economic growth in Bengkulu Province. The Plantation sub-sector has a positive influence on economic growth in Bengkulu Province. The Livestock sub-sector has a positive influence on economic growth in Bengkulu Province The Fisheries sub-sector has a positive influence on economic growth in Bengkulu Province. Simultaneous Hypothesis Testing There is a significant influence of the food crop agriculture sub-sector variables, forestry sub-sector, plantation sub-sector, livestock sub-sector and fisheries sub-sector on economic growth in Bengkulu Province